2022
DOI: 10.1002/dev.22315
|View full text |Cite
|
Sign up to set email alerts
|

Development of anxiety‐like behaviors during adolescence: Persistent effects of adolescent morphine exposure in male rats

Abstract: Epidemiological studies show the prevalence of opioid use, misuse and abuse in adolescents, which imposes social and economic accountability worldwide. Chronic opioid exposure, especially in adolescents, may have lasting effects on emotional behaviors that persist into adulthood. The current experiments were therefore designed to study the effects of sustained opioid exposure during adolescence on anxiety-like behaviors. Adolescent male Wistar rats underwent increasing doses of morphine for 10 days (PNDs 31-40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…Increased anxiety‐like behavior and exploratory behaviors in MS mice had been reported before (Wang et al, 2015). It also has been shown that MS reduces the anxiety‐like behavior of adolescent rats in the OF test (Wang et al, 2015) or induces chronic changes in anxiety‐related behaviors (Kalinichev et al, 2000; Khani et al, 2022). On the other hand, MS can induce less anxiety‐like behavior in teenage rats (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased anxiety‐like behavior and exploratory behaviors in MS mice had been reported before (Wang et al, 2015). It also has been shown that MS reduces the anxiety‐like behavior of adolescent rats in the OF test (Wang et al, 2015) or induces chronic changes in anxiety‐related behaviors (Kalinichev et al, 2000; Khani et al, 2022). On the other hand, MS can induce less anxiety‐like behavior in teenage rats (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It also increases reward‐induced behaviors (Abu & Roy, 2021; Fleites et al, 2022), escalations in dependence, withdrawal, and deliberately drinking morphine throughout gestation, body weight, anxiety‐like behavior, and global behavioral scores in mice (Fleites et al, 2022). Drug abuse throughout the developmental period of adolescence affects the maturation of the nervous system and therefore and may cause long‐term behavioral changes (Khani et al, 2022; Vassoler & Byrnes, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…33 Furthermore, our previous study presented the ineffectiveness of chronic adolescent morphine exposure on animal locomotor activity despite the reduction of anxiety-like behaviour from adolescence to adulthood. 8 According to human epidemiological studies, opioid addiction during adolescence is strongly associated with an increased risk of anxiety disorders throughout life. 34 However, contradictory results have been reported from the findings of others in the form of increased or decreased 35 emotional behavioural profiles, including anxiety-like behaviour during opioid exposure.…”
Section: Aame Increases Epsp-spike Coupling In Ventral Hippocampal Ca...mentioning
confidence: 99%
“…Therefore, this makes adolescents more vulnerable to the neurological consequences of opioid consumption compared with adults 7 . Opioid exposure during adolescence leads to disruption in the process of neural development and its specialization, resulting in permanent changes in the brain structure and cognitive function 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation